Mixed microalgae cultivated in outdoor open pond system under variable weather conditions - Tunku Azmir Shah, Tunku Ainna (2016)
Microalgae are known for its ability to be potential biofuel substituting fossil fuel and as a biomitigation strategy to eliminate excessive amount of carbon dioxide within earth’s atmosphere. Mixed microalgae biodiversity acts as a synthetic ecosystem. Variant species mutually exploits complementary metabolic activities which are used for algal growth, survival and reproduction. This study utilizes mixed microalgae growth (eutrophication) from tilapia fish pond and benefiting the algae for its latent potentials; as a promising alternative for not only fuel, but also animal feed and food supplement. The objectives of this research are; to determine the productivity and the Specific Growth Rate (SGR), to examine the algal succession and species identification, to quantify the biochemical composition (%) and toxicity of the harvested mixed microalgae throughout three different weather conditions during the cultivation process. Productivity and Specific Growth Rate of the mixed microalgae was deliberated via three independent analysis; optical density (680nm), biomass dry weight, and chlorophyll a. The estimation of species concentration (%) was using the Neubauer counting slide and visualized via Olympus BH2 light microscope at 400× and 1000× magnification. Most diatoms and dinoflagellates were identified to species level with the aid of algal taxonomy reference book. Biochemical quantification that was conducted were; soluble protein, Bradford method; carbohydrate, Soluble carbohydrate method; and lipid, modified Bligh and Dyer method. The toxicity analysis was performed by exposing Brine Shrimp (Artemia nauplii) to extracted mixed microalgae as toxicant. An optimization of the algal concentration (mixed microalgae/tap water) % v/v was conducted as preliminary study. Due to good increment in algal growth, two of the highest productivity and SGR; 50 % v/v and 75 % v/v was then cultured in three weather conditions; rainy weather; culture faced rainfall throughout culture period, mixed weather; culture only faced rainfall during several days of culture period, and sunny weather; culture did not face rainfall throughout culture period. The highest productivity; 0.04 ± 0.00 g L-1 d-1 and Specific Growth Rate; 0.21 ± 0.02 μ d-1 documented was from Treatment 2; 75% v/v algal concentration cultured during sunny weather condition. Throughout the 30 days of cultivation (3 complete weather conditions); 4 species were identified during rainy season, 8 species during mixed weather condition and 12 species during sunny weather conditions. Several species did exist predominantly during all three weather conditions, thus, bringing the total number of 13 identified species. Biochemical analyses quantified the highest protein content (%); 46.88±0.23, carbohydrate content (%); 31.36±0.21 and lipid content (%); 29.41±0.24 which was all cultured via Treatment 2 during sunny weather condition. The toxicity analysis proved that the cultured mixed microalgae are suitable for consumption with the LD50 value; 59.33 % when it was exposed to 30 mg L -1 of extracted mixed microalgae which is considered non toxic. Sufficient sunlight irradiation, optimum culture conditions, combined with effective ambient state will generate high algal productivity with infinite potentials. However, the insights on mixed microalgae cultivation and other factors influencing the process could be conducted in future to examine the efficiency of the culture at various treatment levels.